The use of portable fish aggregating devices for pelagic fish in Sunda Strait Water, Indonesia. (May 2019) - Yusfiandayani, R; Nurilmala, M; Nurjanah,; Abdullah, A; Sondita, M F A; Simanjuntak, C P H
Abstract: Portable FADs is a transformation of the conventional FADs which uses the concept of fish responses related to the use of sound frequencies. Portable FADs is a new innovation auxiliary gear in pelagic fishing. The aims of this study are to know the prototype of portable FAD, to know dominant fish compositions of the catches around portable FADs and to analyze total buoyant and sinking force of portable FADs. The study was conducted in laboratory and field experiment in Sunda strait waters. Data analysis were performed by using buoyancy force and sinking force analysis of portable FADs and the composition of the catch. The prototype of portable FADs was made from fiber with dimensions L x W x H = 63 x 43 x 25 cm. The composition of the dominant fish around portable FADs are 83 tails of Rastrelliger sp., 57 tails of Istiophorus platypterus and 51 tails of Euthynnus affinis. Portable FAD has total buoyancy and sinking force of portable FADs are 192.888, 2 GS and GS 179.538, 19.